Perancangan Sistem Informasi Akuntansi Penerbitan Surat Perintah Pencairan Dana (SP2D) Berbasis Desktop Di Kecamatan Cimahi Utara - Anisha Ramandha (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
The purpose of this research is to find out: (1) the Application of data processing systems for disbursement of funds, (2) Solve problems that arise in the process of making a warrant for disbursement of funds (SP2D), and making a request for transfer of funds (NP2D), (3)Development Designing a Budget Bookkeeping System (SISPERAN) by applying Microsoft Visual Studio 2010 software and a Microsoft Access database. In this study, the authors carried out qualitative data analysis using interviews, observation, and literature review. And the system development method uses the waterfall method. From the results of the study, it was found that the problem was in making the order for disbursement of funds (SP2D) and making a memorandum of request for transfer of funds (NP2D) which was still manual, so it was prone to errors in data input, the resulting report was less accurate and the time required was relatively long. The author hopes that by designing this system, it can reduce problems that may occur and can facilitate employees in making SP2D and NP2D.